Operations Strategy Formulation: Shifting from Grasberg Open-Pit Surface Mining to Underground Mining - Sulistyo, Rafiq; Soedjarno, Alibasjah; Simatupang, Togar M. (International Research Journal of Business Studies, 2011)
PT Freeport Indonesia has decided to alter its mining operations from open-pit mining to underground mining in Grasberg. A change of mining area focus directly affects its related departments, and even need new operations strategy to address the transition. Considering its long-term run of mining operations, its strategic issues are assessed by using Slack and Lewis operations strategy model, and decisions are made through the Quantitative Strategic Planning Matrix (QSPM) tool. Previously, the assessment of company’s current business and corporate strategy was conducted by applying SWOT analysis and complemented with the Strategic Factors Analysis Summary (SFAS) as the point-of-reference of the operations strategy.